GENERATION OF CW 243 NM RADIATION AND APPLICATION TO LASER SPECTROSCOPY OF THE STRONTIUM ISOTOPES - Foot, C; Baird, P; Boshier, M; Stacey, D; Woodgate, G (1984)
Intra-cavity second harmonic generation in a ring dye laser using lithium formate monohydrate has been observed to produce tunable cw UV radiation around 243 nm with single frequency powers of up to 1.4 mW. This wavelength region is of particular interest in the context of Doppler-free spectroscopy of atomic hydrogen. The radiation was used to excite an atomic beam of strontium to study the transition 5s2 1S0-4d5p 1P1 of Sr I. The isotope shifts were determined as follows: 88Sr-87Sr 123.7(8) MHz; 88Sr 285.0(8) MHz; 88Sr-84Sr 600.1(9) MHz. The values are compared with results for other lines and muonic isotope shifts to obtain the specific mass shift and field shift in this transition and to study the configuration mixing effects. The hyperfine structure of 87Sr was not resolved, the intervals being very much less than the measured linewidth of 25 MHz. © 1984.